THU0537 Selected Factors of Complement Lectin Pathway Factors in Polish Children with Juvenile Idiopathic Arthriti. (9th June 2015) - Zuber, Z.; Kasperkiewicz, K.; Michalski, M.; Eppa, Ł.; Bartłomiejczyk, M.; Świerzko, A.; Mężyk, E.; Noszczyńska, M.; Cedzyński, M.
Abstract : Background: Juvenile idiopatic arthritis (JIA) is the most common childhood rheumatic disease. Complement system is suggested to contribute to JIA. Mannose-binding lectin (MBL) and ficolin -3 are important factors of innate immunity with ability to initiate the lectin pathway of complement, thanks to co-operation with MASP proteases. Although they are produced in the liver and circulates in the blood, they are also detected extravasculary. They contribute to the clearance of microorganisms as well as apoptotic cells. The mutations in the MBL2 exon 1 and promoter region (designed as O/O+LX/O) as well as FCN3 frame-shift mutation 1637 delC influence significantly proteins' serum level. Objectives: The aim of this study was to evaluate the contribution of the complement lectin pathway system to the pathogenesis of juvenile idiopathic arthritis. Methods: Serum and/or DNA samples were collected from 175 patients with JIA and 98 healthy controls from the St Louis Children's Hospital, Krakow, Poland. Additionally, 55 samples of synovial fluid were obtained. The concentrations and activity of MBL and ficolin-3 were determined in functional ELISA with use of specific antibodies [1, 2]. The single nucleotide polymorphisms in MBL2 gene promoter and exon 1 as well as FCN3 frame-shift mutation 1637 delC were determined using PCR/RFLP methods [1, 2]. Results: The mean age of JIA patients and healthy controls was 12 and 9 years, respectively (p=0, 01). The serum levels of MBL and ficolin-3 in JIA patients did not differ from levels in the control group. The MBL2 gene polymorphism was analysed in 112 JIA patients and 98 healthy controls. The frequency MBL deficiency-associated genotypes (so called O/O+LXA/O) was 17, 8% and 16, 3%, respectively. Additionally, no differences in the frequency of FCN3 1637delC mutation was noticed (5 and 5, 6%, respectively). Concentrations of both MBL and ficolin-3 correlated with CRP levels in patients group (p=0, 02). No difference in MBL level in JIA patients and controls representing MBL2 AA genotype were found. Although MBL and ficolin-3 levels did not differ between the groups, the activity of MBL-MASP-2 complexes was significantly higher in JIA patients than in controls (p=0, 002). MBL, its active complex with MASPs and ficolin-3 were also detected in synovial fluid samples from JIA patients and their levels correlated significantly with those in sera (p<0, 0001). Conclusions: The presence of factors of lectin pathway in synovial fluid may suggest their contribution to development of juvenile idiopatic arthritis. Disclosure of Interest: None declared